2021
DOI: 10.4012/dmj.2020-364
|View full text |Cite
|
Sign up to set email alerts
|

Color adjustment potential of single-shade resin composite to various-shade human teeth: Effect of structural color phenomenon

Abstract: This study evaluated the effect of the structural color phenomenon in resin composites (RCs) on the color adjustment of restorations by investgating their color reproduction performance in human incisors of various shade. Cervical cavities were filled with a singleshade RC with 260 nm spherical fillers (Omnichroma (OMN)), conventional A2-shade RCs (Estelite Σ Quick or Clearfil AP-X), or experimental RCs with 5-50 nm fumed silica fillers (R1) and 100 nm spherical fillers (R2). Color parameters (L*C*h*) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 47 publications
3
67
0
4
Order By: Relevance
“…Within the limitations of this study, Omnichroma was used as a single-shade resin composite, being one of the most clinically successful single-shade composites. It is considered one of the most widely researched singleshade material, with several research work investigating its color adjustment potential [6,9,[20][21][22], and optical properties [23,24]. The color stability of Omnichroma under accelerated aging conditions using Xenon Arc UV light sources to simulate exposure to natural sunlight [25] and 1 week staining in tea [26] were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Within the limitations of this study, Omnichroma was used as a single-shade resin composite, being one of the most clinically successful single-shade composites. It is considered one of the most widely researched singleshade material, with several research work investigating its color adjustment potential [6,9,[20][21][22], and optical properties [23,24]. The color stability of Omnichroma under accelerated aging conditions using Xenon Arc UV light sources to simulate exposure to natural sunlight [25] and 1 week staining in tea [26] were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, universal chromatic RBCs were developed to adapt aesthetically to every situation and every patient in order to do justice to the variety of shades of the teeth and restorations [ 9 , 10 ]. An improved blending effect of such RBCs into the environment has indeed been attested [ 11 , 12 , 13 ], with the caveat, however, that this effect is cavity-size dependent [ 14 , 15 , 16 ]. The way in which color is created in universal chromatic RBCs is innovative, as it is not only induced by selective light absorption via pigments, as usual in dental materials, but also by selective light reflection via particularized microstructures [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 A comparison between a single-shade composite and two pigmented ones demonstrated a stronger chameleon effect in the former. 5 In the same study, a contribution of structural color to the chameleon effect was suggested.…”
Section: Introductionmentioning
confidence: 87%